Effectiveness of School-Based Physical Activity Programmes on Cardiorespiratory Fitness in Children: A Meta-Analysis of Randomised Controlled Trials - Garcia-Hermoso, A (BMJ Publishing Group, 2018)
Objective To conduct a meta-Analysis of randomised controlled trials aimed at testing whether school-based physical activity programmes improve cardiorespiratory fitness (CRF) in children. Design Systematic review with meta-Analysis. Data sources Using keywords, we performed a computerised search in five databases: MEDLINE, EMBASE, CINAHL, Web of Science and SportDiscus. Eligibility criteria for selecting studies Studies that assessed the effectiveness of school-based physical activity programmes on improving CRF in children (3-12 years old). We selected interventions that included an additional physical activity programme and not only a physical activity educational component. The reference lists of selected full-Text articles and systematic reviews were also searched for relevant studies. Pooled effect size (Hedges′ g) was calculated assuming a random-effects model. Results Twenty trials with 7287 healthy children aged 3-12 years were included in the meta-Analysis. School-based physical activity interventions with aerobic games and activities were associated with a significant small increase in CRF (Hedges′ g=0.22; 95% CI 0.14 to 0.30; p<0.001). Based on subgroup analysis, the increase in CRF was significant in girls (Hedges′ g=0.25; 95% CI 0.13 to 0.37; p<0.001), but not in boys (Hedges′ g=0.02; 95% CI 0.10 to 0.14; p=0.731). Summary Moderate quality evidence supports the effectiveness of school-based physical activity interventions on improving CRF in children. Trial registration number Protocol PROSPERO registration number CRD42016050173. © © Article author(s) (or their employer(s) unless otherwise stated in the text of the article) 2018. All rights reserved. No commercial use is permitted unless otherwise expressly granted.